Transformasi Tata Kelola Pemerintahan Desa Akulturasi Antara Peraturan Adat dan Digitalisasi (Studi Pada Desa Kanekes Kecamatan Luwidamar Kabupaten Lebak) - Apud, Eli Apud Saepudin; Handayani, Putri; Amilia, Rizki (FIA Unkris Press, 2023)
The development of technology that is getting more advanced greatly facilitates human activities, both in the village government administration system, public services that were originally manual now have a computerized system so as to facilitate public service activities. This is not spared by the community in Baduy, which is known to live far from the development of the times. The purpose of this research is to explain how Baduy Community starts to follow the development of modern technology in the digital era, but still follows some existing customary regulations. One of the technological developments that began to be used by the Baduy Community is the payment process with the QRIS payment system. This research method uses a qualitative descriptive method. The results of the study show that with the entry of modernization culture from outside, it does not mean that the Baduy Community completely forgets the existing customary regulations. Therefore, acculturation is needed by trying to enter modernization culture without eliminating the culture that previously existed. The entry of modern culture can actually coexist with the existing culture without shifting the prevailing customs